Iglesia parroquial, Bagsvaerd, Dinamarca : Jørn Utzon [1973-1976] - Isasi, Justo F. (2002)
Obra donde se destaca el cerramiento con cubiertas de cristal en la estructura rectangular de hormigón
Keywords: ARQUITECTURA RELIGIOSA; IGLESIAS; BAGSVAERD; DINAMARCA; SIGLO XX; HISTORIA; CRITICA; HORMIGON; ESTRUCTURAS